Reduction of experiential avoidance with ACT and FAP group therapies in transdiagnostic groups - Ruiz Sánchez, Juan José (2019)
We present two modalities of third generation contextual therapies in their group therapy format applied to groups of people with diverse transdiagnostic problems in a public context of attention to mental health. In both groups of therapies an intervention design of 12 sessions with experiential exercises during 3 months is used. The results of this study indicate that both group modalities are effective in reducing experiential avoidance along with other aspects, a reduction that does not occur when the results are compared with those in the individual therapy control group. The results propose a promising path for the application of group contextual therapies in public contexts.